Daratumumab: A new future for AL-Amyloidosis and Multiple Myeloma - Pardinhas,Clara (2020)
Concomitant development of symptomatic amyloid light-chain (AL) amyloidosis and multiple myeloma (MM) is rare and has a poor survival rate. Introduction of thalidomide and bortezomib, a proteasome inhibitor, has improved the survival of patients with MM; however, it has not cured the disease. Nevertheless, monoclonal antibodies may treat the disease using an immunotherapeutic approach. This report describes the case of a 39-year-old man with MM IgG lambda, heavily treated with multiple QT cycles and two hematopoietic stem cell transplants, who developed light chain amyloidosis. After an interdisciplinary discussion, daratumumab was initiated. Approximately 24 months later, he presents complete remission of the disease, normal renal function and no associated symptoms.